The Accuracy of Modified Risk Malignancy Index (RMI) in Predicting Malignancy of Epithelial Type Ovarian Cancer: Akurasi Modifikasi Risk of Malignancy Index dalam Memprediksi Keganasan Tumor Ovarium Tipe Epitel - Esfi Triana; Defrin Defrin; Joserizal Serudji; Adriswan Adriswan (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective:To investigate the accuracy of modified Risk of Malignancy Index (RMI) in predicting malignancy of epithelial type ovarian tumour. Method: This research was comparative research using cross-sectional study design, which compared RMI modification and RMI method in predicting malignancy of epithelial type ovarian tumour. The sampling technique was consecutive sampling. This research was conducted on October 2017 until samples were fulfilled in Obstetrics and Gynecology Division of RSUP Dr. M. Djamil and Laboratory of RSUP Dr. M Djamil in Padang. Chi-square test was used to compare specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), negative likelihood ratio (NLR, and accuracy of RMI modification and RMI with 95% CI (pâ‰¤0,05). Results: A total of 61 subjects were recruited in this study. Sensitivity, specificity, PPV, NPV, PLR, NLR, and accuracy RMI modification scoring was 90.5%, 82.5%, 73.1%, 94.3%, 5.1, 0.1, dan 85.2%. Sensitivity, specificity, PPV, NPV, PLR, NLR, and accuracy RMI scoring was 66.7%, 70%, 53.8%, 80%, 2.2, 0.4, and 70% Conclusions:Modified RMI scoring method was more accurate in predicting the malignancy of ovarian type epithelial tumours than RMI. Keywords: CA125, malignancy, ovarian tumor,pelvic mass, RMI, Abstrak Tujuan: Mengetahui akurasi Risk of Malignancy Index (RMI) dalam prediksi keganasan tumor ovarium tipe epitel. Metode: Penelitian ini merupakan penelitian komparatif dengan desain penelitian potong lintang yang membandingkan metode RMI modifikasi dan RMI dalam prediksi keganasan tumor ovarium tipe epitel. Jumlah sampel sebanyak 61 orang. Teknik pengambilan sampel berurutan. Penelitian di mulai pada bulan Oktober 2017 hingga jumlah sampel terpenuhi di Departemen Obstetri dan Ginekologi RSUP Dr. M Djamil dan Laboratorium RSUP Dr. M Djamil Padang. Untuk membandingkan spesifisitas, sensitivitas, nilai duga positif (NDP), nilai duga negatif (NDN), rasio kemungkinan positif (RKP), rasio kemungkinan negatif (RKN), dan akurasi RMI modifikasi dan RMI digunakan uji chi-square dengan 99% CI (pâ‰¤0,01). Hasil: Sensitivitas, spesifisitas, NDP, NDN, RKP, RKN, dan akurasi skoring RMI modifikasi adalah 90,5%, 82,5%, 73,1%, 94,3%, 5,1, 0,1, dan 85,2%. Sensitivitas, spesifisitas, NDP, NDN, RKP, RKN, dan akurasi skoring RMI adalah 66,7%, 70%, 53,8%, 80%, 2,2, 0,4, dan 70%. Kesimpulan: Metode skoring RMI modifikasi lebih akurat dalam memprediksi keganasan tumor ovarium tipe epitel dibandingkan RMI. Kata kunci: CA125, keganasan, massapelvik, RMI, tumor ovarium